Forelimb preferences in human beings and other species: multiple models for testing hypotheses on lateralization - Versace, Elisabetta; Vallortigara, Giorgio (Frontiers in Psychology, 2015)
Consistent preferences in the use of right/left forelimbs are not exclusively present in humans. Functional asymmetries in forelimb use have been widely documented in a variety of vertebrate and invertebrate species. A matter of debate is whether non-human species exhibit a degree and consistency of functional forelimb asymmetries comparable to human handedness. The comparison is made difficult by the variability in hand use in humans and the few comparable studies conducted on other species. In spite of this, interesting continuities appear in functions such as feeding, object manipulation and communicative gestures. Studies on invertebrates show how widespread forelimb preferences are among animals, and the importance of experience for the development of forelimb asymmetries. Vertebrate species have been extensively investigated to clarify the origins of forelimb functional asymmetries: comparative evidence shows that selective pressures for different functions have likely driven the evolution of human handedness. Evidence of a complex genetic architecture of human handedness is in line with the idea of multiple evolutionary origins of this trait.